Liver Kinase B1 Functions as a Regulator for Neural Development and a Therapeutic Target for Neural Repair - En Huang; Shuxin Li (Cells, 2022)
The liver kinase B1 (LKB1), also known as serine/threonine kinase 11 (STK11) and Par-4 in C. elegans, has been identified as a master kinase of AMPKs and AMPK-related kinases. LKB1 plays a crucial role in cell growth, metabolism, polarity, and tumor suppression. By interacting with the downstream signals of SAD, NUAK, MARK, and other kinases, LKB1 is critical to regulating neuronal polarization and axon branching during development. It also regulates Schwann cell function and the myelination of peripheral axons. Regulating LKB1 activity has become an attractive strategy for repairing an injured nervous system. LKB1 upregulation enhances the regenerative capacity of adult CNS neurons and the recovery of locomotor function in adult rodents with CNS axon injury. Here, we update the major cellular and molecular mechanisms of LKB1 in regulating neuronal polarization and neural development, and the implications thereof for promoting neural repair, axon regeneration, and functional recovery in adult mammals.